2013
DOI: 10.3389/fncel.2012.00064
|View full text |Cite
|
Sign up to set email alerts
|

Generating regionalized neuronal cells from pluripotency, a step-by-step protocol

Abstract: Human pluripotent stem cells possess the potential to generate cells for regenerative therapies in patients with neurodegenerative diseases, and constitute an excellent cell source for studying human neural development and disease modeling. Protocols for neural differentiation of human pluripotent stem cells have undergone significant progress during recent years, allowing for rapid and synchronized neural conversion. Differentiation procedures can further be combined with accurate and efficient positional pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 8 publications
2
50
2
Order By: Relevance
“…Thus, monolayer cultures of NSCs/NPCs would be advantageous. Several protocols to derive NSCs/NPCs efficiently from hES cells or iPSCs currently utilize Noggin to induce neuronal differentiation, 19,20 but the need for Noggin significantly increases the cost of the differentiation process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, monolayer cultures of NSCs/NPCs would be advantageous. Several protocols to derive NSCs/NPCs efficiently from hES cells or iPSCs currently utilize Noggin to induce neuronal differentiation, 19,20 but the need for Noggin significantly increases the cost of the differentiation process.…”
Section: Introductionmentioning
confidence: 99%
“…When transplanted in the lesioned rodent striatum, DA neurons from human fVM and PSCs show extensive reinnervation of striatal and extra-striatal target structures (Brundin et al, 1986;Sanchez-Pernaute et al, 2005;Thompson et al, 2005;Kirkeby et al, 2012;Grealish et al, 2014), and, when grafted in the SN, they project axons over long distances and reinnervate the relevant A9 and A10 host target structures (Grealish et al, 2014), as was observed for rodent DA neurons (Thompson et al, 2009).…”
Section: Axonal Outgrowth and Migration In The Host Brainmentioning
confidence: 91%
“…Characterization of the cells showed that DA neurons express midbrain DA neuron markers such as NURR1 and LMX1A, LMX1B, FOXA2, OTX2, CORIN, PITX3, factors that control specification and differentiation of midbrain DA neurons during mouse development (reviewed in Arenas et al, 2015), and GIRK2, which is the A9-specific marker (Thompson et al, 2005). They also express tyrosine hydroxylase (TH), and the dopamine transporter (DAT), and they produce dopamine, confirming that they are functional DA neurons (Kriks et al, 2011;Kirkeby et al, 2012;Arenas et al, 2015).…”
Section: Da Neurons Isolated From Primate Pscs or By Direct Reprogrammentioning
confidence: 99%
See 1 more Smart Citation
“…This will require robust and appropriate fate restriction into more specialized lineages and their survival and appropriate functional integration into existing host circuitry after transplantation. Kirkeby et al (2013) contribute a detailed methodological paper on the generating regionally specified neurons, by way of controlling dorso-ventral and rostrocaudal patterning of stem cells. Arber and Li (2013) provide a more focused review of the literature on understanding cortical interneuron development and the progress in protocols to yield interneuron subpopulations from pluripotent stem cells for the purpose of transplantation into models of epilepsy.…”
mentioning
confidence: 99%